Importance of the 2020 Croatia Earthquakes GIS-based Building Usability Database: Building Damage - Kadić, Alen (Crisis Management Days, 2024)
There are still many existing gaps regarding earthquakes and each new earthquake brings out new findings and therefore presents a new opportunity to fill those gaps. Even though earthquakes are geographically limited hazards, the findings are usually globally applicable, as was the case with 2020 Croatia Earthquakes. One of the key findings after 2020 Croatia Earthquakes was the role and importance of GIS-based databases in response and recovery after disasters, especially earthquakes. This area is not the focus and is generally not sufficiently studied and emphasized in the field of earthquake engineering and emergency management. They have a supporting role to the Building Damage and Usability Assessments, but their potential is much greater, and this has already been proven in past emergencies and studies. Therefore, it is important to study and report on real-world experiences that confirm the importance of GIS-based databases. The experiences after the 2020 Croatia Earthquakes have been studied and reported in several studies. Most notably in one from City of Zagreb experts (Jerković and Škreblin, 2021), but also several others from the group of authors from Faculty of Civil Engineering, University of Zagreb and Croatian Centre for Earthquake Engineering (Atalić et al. 2021; Atalić et al. 2022; Šavor Novak et al.; Uroš et al., 2020) This study serves as an extension focusing on the follow-up activities after their studies and using these activities and database as a case study for other similar databases globally, mainly by using synthesis and generalization. The study is mainly qualitative with several quantitative elements, such as numeric statistics of the implemented activities. The 2020 Croatia Earthquakes GIS-based Building Usability Database can serve as an example of numerous good practices, but also of numerous problems that have occurred and from which the global community can gain new insights or confirm the existing ones. The 2020 Croatia Earthquakes and the associated GIS-based Building Usability Database can serve as a great example for similar national emergency management systems that have a very low level of earthquake risk mitigation and preparedness. The overall response and recovery after the event illustrate the lack, but also the importance of risk reduction and preparedness, which can greatly facilitate and simplify post-disaster emergency management. On the other hand, the complex and difficult situation after the 2020 Croatia Earthquakes was mitigated by high-quality “ad hoc” solutions, which included the GIS-based Building Usability Database. The database was essentially created essentially overnight during the first hours after the earthquake and updated again overnight after the 2020 Petrinja Earthquake and its catastrophic consequences. But the database was not only sufficient to fulfil its main purpose, but it could also serve many other purposes, some of which were not even imagined when it was created. Not only the primary database could not initially support other activities, but also numerous acts and decisions that were passed from the first days after the earthquake and were based on it (alternative accommodation, donations/humanitarian aid prioritization, reconstruction process rights, utility bill exemptions, bank loans approvals and many others), and all of them involved a lot of pressure and responsibility (Kadić, 2023). However, a bigger problem was the fact that additional capabilities were needed within the database and the reason for this is new activities that are part of the reconstruction process. During the reconstruction process, all buildings underwent a detailed assessment, in which their usability was changed according to the results of the assessments. The decision was made to form the Croatia Earthquakes’ GIS-based Building Usability Database. During the formation, the accumulated knowledge from two existing databases (Zagreb and Petrinja Earthquake) was used and, more importantly, both databases served as a starting point for the new comprehensive Building Usability Database. In addition to the layers of the existing databases, a new layer had to be created to enable the input of the new data connected to usability changes in the reconstruction process. For that purpose, some completely new attributes (type of reconstruction, document type) as well as new values in existing attributes (demolished and reconstructed in usability categories) were added to the database. This even proactively ensured that all future reconstruction and database requirements were covered. Over time, there was a growing number of entries in the new reconstruction layer in the Building Usability Database. Multiple inputs for the same building were also no exception as the buildings went through different stages of reconstruction. This and the initial inputs from Buildings Damage and Usability Assessments required an expert understanding of the gradation of input types to accurately interpret the building usability category in real time. There were many other issues whose resolution had to wait for the database to be stored on the official state server, including the use of the online application form for the reconstruction process, the overlapping of existing databases/layers, quality control and improvement, the possibility of using license bundles (for numerous users) for which the government provided the funding. CCEE was granted access to the official state server in January 2023. The official state server is certainly going to allow the database to reach its full potential and solve all the forementioned problems, but also to save considerable additional resources that had to be invested. This database must become a basis for all future activities of the CCEE, but also for all activities related to buildings in the Republic of Croatia, much wider than just earthquake response and recovery. To ensure this, a proactive and comprehensive approach is also needed. In addition to the activities in the response and recovery phase, the CCEE also has numerous activities in the prevention and preparedness phases. All these activities must be included in the comprehensive building database. This is also important Republic of Croatia, not only CCEE. It has to use its sources and support CCEE in suing all their experience and further improving the existing database to reach its full potential and long-term use.